Stress wave propagation across jointed rock mass under dynamic extension and its effect on dynamic response and supporting of underground opening - Zhu, Jianbo; Li, Yashi; Peng, Qi; Deng, Xifei; Gao, Mingzhong; Zhang, Jianguo (Tunnelling and underground space technology, 2021)
•Extension/compression-first wave transmission differs owing to joint opening.•Joint tensile strength determines stress wave propagation under dynamic extension.•Rock bolt and shotcrete lining effectively support opening against dynamic extension. Rock joints are prone to open and fail when subject to severe dynamic extension, which might result in spalling of surrounding rock and collapse of underground openings. However, the understanding of dynamic response of rock joints and underground openings subject to tensile stress wave is still at its infancy. To investigate the effect of tensile wave on the response, stability and supporting of underground openings in jointed rock mass, numerical modelling was carried out herein with the DEM-based universal distinct element code (UDEC) after its validation using explosion testing measurements. Results showed that joint tensile strength has significant effects on stress wave propagation if it is lower than the amplitude of tensile stress wave in the shallow rock mass, where joint opening will occur, no significant portion of wave energy could transmit through the joint, and the transmission coefficient for tension-first wave is lower than that for compression-first wave. The buried depth of underground opening and joint properties including stiffness, spacing and dip angle as well as crossing angle between joint sets could significantly influence stress wave propagation and dynamic responses of underground openings under dynamic extension. In addition, installation of rock bolts with appropriate number and length and shotcreting with sufficient thickness could effectively reinforce the surrounding rock and reduce the area of disturbed zones when against dynamic extension. The findings in this study could be of great significance for the design, supporting and stability evaluation of underground openings.